The encyclopedia of cooking skills & techniques - MacMillan, Norma; Clements, Carole (Lorenz Books, 2011)
Teaches the basic techniques and how to use them. This guide offers over 200 recipes, from simple soups to delectable desserts. It reveals the secrets of classic techniques, as well as modern innovations. It contains hundreds of recipe variations and ideas, tips for coping with tricky procedures, and helpful advice on ingredients and equipment